Strategi Pembelajaran Instruktur Menurut Warga Belajar pada Pelatihan Menyulam - Aldi Saputra; Syafruddin Wahid; Ismaniar Ismaniar (Universitas Negeri Padang, 2018)
The background of this research is the success of learning process of embrioder at HP3 Padang Pariaman. The purpose of this research is to describe instructor's learning strategy, that is: (1) teaching stage, (2) teaching approach, (3) teaching principle. This type of research is descriptive quantitative. The populations of the study consist of thirty-five peoples. The technique in this research is random sampling method. The number of samples in this study were twenty-five participants. Techniques of data collection are questionnaires, while questions is used as data collection tool. The results showed that the instructor's learning strategy according to the study population is interesting, it can be seen from the aspect: (1) teaching stage, (2) teaching approach, (3) teaching principle. Suggestions for learning strategy of these three aspects can be maintained and further enhanced by training Instructor.